CHARACTERIZATION OF ANTIBACTERIAL BIOACTIVE COMPOUNDS FROM KUSAMBI LEAF EXTRACT (Schleichera oleosa (L) Oken) - Sanan, Antonius Oenunu; Murti, Yosi Bayu; Hertiani, Triana (Journal Pharmaceutical Science and Application, 2024)
Background: The kusambi plant is traditionally used by people to treat various diseases. This plant is thought to contain various secondary metabolites with various pharmacological activities, including antibacterial. Objectives: This study aims to determine the antibacterial activity of various extracts using n-hexane, ethyl acetate, and 96% methanol as solvents against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922 bacteria and identify what groups of compounds are contained in the kusambi leaf extract. Method: Kusambi leaves were extracted with Soxhlet using n-hexane, ethyl acetate, and 96% methanol (1:4 w/v). Activity testing uses the agar diffusion method, and compound class testing uses the TLC (thin layer chromatography) method and spray reagents. Results: The research showed the highest yield was 22% for methanol extract, 12% for N-hexane extract, and 20% for ethyl acetate extract. Methanol extract activity test Kusambi leaves show moderate intensity inhibitory activity against bacteria S.aureus bacteria, while bacteria E.coli did not show inhibitory activity. The most significant inhibition zone diameter in the ethyl acetate extract was 9.22 mm with a concentration of 10?g/mL, the methanol extract had an inhibition zone diameter of 8.82 mm with a concentration of 10 ?g/mL, and the leaf N-hexane extract had no inhibition zone. The identification results of the compound groups were flavonoids, alkaloids, phenols, steroids, and triterpenoids, as proven by the TLC method and spray reagents. Conclusion: Kusambi leaf extract using ethyl acetate solvent has inhibitory activity against bacteria S.aureus and contains flavonoids, phenols, steroids, alkaloids, and triterpenoids. Keywords:  Kusambi plant; antibacterial; secondary metabolite compounds.